Retrospective, single center evaluation of transperineal prostate biopsy omitting antibiotic prophylaxis and omitting periinterventional screening for bacteriuria - Leboutte, Francois; Schykowski, Tim; Van de Plas, Jeroen; Lemmer, Oscar; Neisius, Andreas (World journal of urology, 2025)
Purpose Although the pursuit of effective and safe early detection methods for prostate cancer has led to advancements in non-invasive tools, there are approximately one million prostate biopsies per year performed annually in the EU [11]. The use of the transperineal approach to prostate biopsy is increasing because it offers a significantly reduced incidence of post-biopsy sepsis complications compared to transrectal biopsies and therefore is the recommended approach in the European Association of Urology guidelines. However, the consensus on the standard of care for antibiotic prophylaxis in some or all transperineal biopsy cases is only beginning to be established. As with transrectal biopsies, there are concerns about antibiotic stewardship, antibiotic side effects and labor and material costs associated with prophylaxis. Methods This retrospective study analyzed 636 patients who underwent transperineal prostate biopsies without the use of antibiotic prophylaxis between January 2019 and August 2020. The primary endpoint was the rate of postinterventional infectious complications, with secondary endpoints including the rate of general complications and associated risk factors. Results The rate of all complications was 1.9%. There were 7/636 (1.1%) infectious complications, of which 3 (0.50%) were prostatitis, 1 (0.16%) was epididymitis, 2 (0.3%) were infections resulting in hospitalization and 1 (0.16%) urosepsis with ICU care. No identified risk factors were associated with infectious complications or post-interventional bleeding. Notably, the cohort was not systematically screened for bacteriuria before biopsy, and patients usually categorized as high risk for post-biopsy complications were not excluded. The rates of infectious complications and sepsis were lower than that reported for transrectal biopsies with antibiotic prophylaxis. Conclusion This study supports the relative safety of omitting antibiotic prophylaxis in transperineal prostate biopsies, showcasing a minimal infectious complication rate. The findings contribute to the ongoing discourse on antibiotic stewardship, emphasizing the need for judicious use to mitigate resistance, avoid allergic side effects and decrease the labor and material costs associated with transperineal prostate biopsy.